Scaling out Solar Pump Irrigators’ Cooperate Enterprise (SPICE) model in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The Solar Pump Irrigators’ Cooperate Enterprise (SPICE) tested and evaluated in the states of Gujarat and Bihar in India by IWMI and CCAFS in collaboration with Tata Trust is being scaled out by the Government of India through a new multi-billion-dollar scheme to implement solarisation of farm irrigation. As per the scheme, the Government of India, Ministry of New and Renewable Energy (MNRE) plan to provide 2.75 million solar pumps to the individual farmers or/and farmers’ cooperatives across India.